CO2 emission evaluation of yard tractors during loading at container terminals. (June 2017) - Yu, Hang; Ge, Ying-En; Chen, Jihong; Luo, Lihua; Tan, Caimao; Liu, Ding
Highlights: Aim to offer a method for evaluating the emissions from yard tractors during loading. Queuing theory is used in the model to capture the behavior of tractor arrivals. Emissions from yard tractor are closely related to the location of export containers. Identify potential measures to reduce transport emissions with the research findings. The emissions from yard tractors are evaluated based on the forecast arrivals. Abstract: CO2 emission generated by yard tractors at container terminals have been proven to be one of the main sources of pollution from maritime transportation. This paper aims to offer a method for evaluating the emissions from yard tractors during loading. First, an assignment model of export containers is built to capture the behavior of tractor arrivals at each block when the loading begins and the queuing theory is used to model the congestion happening in the yard. Second, emissions from yard tractors are evaluated based on the forecast arrivals. The emissions are categorized into two types: one from those tractors which are moving at normal speed and the other from those tractors sitting in traffic jam or at the stop-and-go state. Terminals with different calls and diversified storage utilization are simulated to show the performance of the proposed method and identify potential measures for traffic management aiming to reduce transport emissions. It is shown that the emissions from the yard tractors are closely related to the location of export containers and should be a main concern in operating a busy terminal.